SISTEM INFORMASI LAPORAN PEKERJAAN PROACTIVE MAINTENANCE TANGIBLE BERBASIS ANDROID STUDI KASUS PT TELKOM AREA UBIS KEDUNGHALANG - Ali Ashabulah; Dahlia Widhyaestoeti; Jejen Jaenudin (Universitas Widyatama, 2020)
PT TELKOM Ubis (Unit Bisnis) Kedunghalang is one of the areas entered in the Witel (Wilayah Telekomunikasi) Bogor Regional 2, Proman (Proactive Maintenance) Tangible is an activity of maintenance or improvement of assets AlPro (Alat Produksi) that is outside the office, in Ubis Kedunghalang itself began to active Proman tangible in August 2019. The current running system for reporting Proman tangible using Telegram social media with the result of photo evidence that has been edited first. The research aims to revamp the system in reporting tangible activities, using Android-based applications built with ionic frameworks and JavaScript programming, the Android itself is very versatile and suitable for out-of-office technicians. The advantage of this application technician can directly create a report when its teammates tidy up the AlPro Asset network (production tool) by directly being able to upload evidence photos and the system can automatically auto-tagging the location.